Community structure of shallow tropical reefs undergoing invasion by Tubastraea spp. in a Brazilian Marine Protected Area - Yollanda Carolina da Silva Ferreira Vançato; Joel Creed; Beatriz Grosso Fleury (Aquatic Invasions)
Invasive sun corals (Tubastraea spp.) are spreading along the Brazilian coast where they compete for space with native species, produce chemical compounds with antifouling and anti-predation properties and modify community structure and function. The tropical rocky shores of the Ilha Grande Bay were the first to be invaded in the southwest Atlantic and the Tamoios Marine Protected Area (MPA) within the bay was directly in the path of the spread of Tubastraea. MPAs aim to conserve biodiversity, preventing habitat loss and fragmentation and maintain healthy ecosystems. As healthy communities might better resist invasion the aim of this study was to investigate to what extent the benthic communities of the MPA are resisting the invasion. Baseline data on the abundance of the invasive corals Tubastraea spp. and community structure (cover) were quantified at eight sites over six years. The benthic communities were dominated by multispecies algal turfs, the mat-forming zooantharian Palythoa caribaeorum and the red alga Asparagopsis taxiformis and fell into five community groups two of which contained Tubastraea spp. The number of invaded sites increased over time as did the abundance of Tubastraea spp. in the communities. Tubastraea spp. sequentially invaded the studied communities within the MPA independently of differing community compositions – i.e. they did not offer better biotic resistance than unprotected areas. This was facilitated by the patchy nature of the communities which allowed Tubastraea spp. to get a foothold by initially avoiding species such as P. caribaeorum which offer greater biological resistance. At one site a significant reduction in Tubastraea spp. was detected after mechanical control. We conclude that the MPA’s status as a conservation unit was important to attract research and thus for establishing a baseline, quantifying change due to the invasion and focusing limited management resources, but not in providing significant biotic resistance to the invasion.